NR4A1 destabilizes TNF mRNA in microglia and modulates stroke outcomes - Yao, Yao (PLoS biology, 2023)
Microglia play a dual role in stroke depending on their pro-inflammatory and anti-inflammatory polarization. A study in PLOS Biology identifies a new mechanism, through which the transcription factor NR4A1 negatively regulates TNF expression in microglia.